Preparation and characterization of a novel ionizing electromagnetic radiation shielding material: Hematite filled polyester based composites - Belgin, E. Eren; Aycik, G. A.; Kalemtaş, Ayşe; Pelit, A.; Dilek, D. A.; Kayak, M. T. (Pergamon-Elsevier Science Ltd, 2015)
Isophthalic polyester (PES) based and natural mineral (hematite) filled composites were prepared and characterized for ionizing electromagnetic radiation shielding applications. Density evaluation and microscopic studies of the composites were carried out. Shielding performances of the composites were investigated for three different IEMR energy regions as low, intermediate and high. The mass attenuation coefficient of the prepared composites reached 98% of the elemental lead. In addition, the studied composites were superior to lead by virtue of their non-toxic nature. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Ionizing electromagnetic radiation; Radiation shielding; Composite shielding; Polymer composite; Hematite